2010
DOI: 10.5114/aoms.2010.14246
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase: potential relationship to idiopathic hypertension

Abstract: Catecholamine signaling pathways in the peripheral and central nervous systems (PNS, CNS, respectively) utilize catechol-O-methyltransferase (COMT) as a major regulatory enzyme responsible for deactivation of dopamine (DA), norepinephrine (NE) and epinephrine (E). Accordingly, homeostasis of COMT gene expression is hypothesized to be functionally linked to regulation of autonomic control of normotensive vascular events. Recently, we demonstrated that morphine administration in vitro resulted in decreased cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Intrarenal COMT levels of normotensive rats were lower than those of spontaneously hypertensive rats . The intracellular COMT mRNA levels were increased by administration of epinephrine and decreased by administration of morphine that suppressed sympathetic nerve activity . These results were considered by negative feedback against sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 93%
“…Intrarenal COMT levels of normotensive rats were lower than those of spontaneously hypertensive rats . The intracellular COMT mRNA levels were increased by administration of epinephrine and decreased by administration of morphine that suppressed sympathetic nerve activity . These results were considered by negative feedback against sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 93%
“…These enrichment analyses were used to explore the molecular mechanisms of enriched genes involved in the occurrence and advancement of HD. Signaling pathways include signaling by GPCR [56] [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-Omethyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA [112], HOXB9 [113], TGM2 [114], LRRK2 [115], ROS1 [116] NKX6-1 [141], SLC22A3 [142], CADM2 [143], FREM1 [144], TWIST2 [145], WNT16 [146], KISS1 [147], TMEM176B [148], MYL9 [149], IL7R [150], MBP (myelin basic protein) [151], GPR37 [152], ACAN (aggrecan) [153], SHH (sonic hedgehog signaling molecule) [154], HOXD9 [155], PROK1 [156], AGTR1 [157], TIE1 [158], P2RX7 [159], NTSR1 [160], VTN (vitronectin) [161], SIRT2 [162], RBP4 [163] [178], HLA-DRB1 [179], NKX2-3 [180], CD74 [92], HLA-DRA [181], VWF (von Willebrand factor)…”
Section: Discussionmentioning
confidence: 99%
“…109 This is also somewhat evident from the COMT data, which involve ADHD behavioral states and EDs. 110 , 111 Taken together, although ADHD is complex and multifaceted as are EDs, it appears that they may represent a logical comorbidity. Hence, early diagnostic indicators for ADHD may be at hand in the form of novel discoveries in gene expression patterns.…”
Section: Discussionmentioning
confidence: 99%